(untitled) (Research, Society and Development, 2020)
The research aims to understand the formation and how the knowledge of teachers who teach in the literacy of Persons Deprived of Liberty in the penitentiary system of Mato Grosso is constituted. Its methodological proposal is the case study whose data collection instruments are the observation of the researched space, a structured questionnaire for the identification and selection of participants and a semi-structured interview. The proposal involves teachers who work in the first segment of Youth and Adult Education and prioritizes the experiences lived and acquired in the space mentioned, which is different from the usual schools. The authors who support this study are: Tardif (2012); Freire (2011); Arroyo (2008). The locus of the research is a state school located in Cuiabá that serves people deprived of their liberty, whose participants are teachers from the 1st segment of Youth and Adult Education. The results showed that there is no offer of initial or continuing education for the area in which they work and that the knowledge that subsidizes all their teaching activities in the penitentiary system, comes from the experience acquired in the course of 10 years supported by the knowledge acquired in theories.